LTE and NLTE LITHIUM ABUNDANCES IN ATMOSPHERES OF LITHIUM RICH RED GIANTS - Pavlenko, Ya. V.; Yakovina, L. A. (Одеські астрономічні публікації, 2017)
Results of the computations of the statistical balance of lithium in atmospheres of a sample lithium rich G-K giants are discussed. Investigations were performed for QO-level model lithium atom by complete linearisation method. Blocking effect due to the radiation absorption by atoms, ions and molecules was taken into account. The abundances of lithium in atmospheres of 13 red giants have been reconsidered taking into account NLTE effects.